Nerve terminals at the human corneoscleral limbus. Issue 4 (15th December 2017) - Al-Aqaba, Mouhamed A; Anis, Fady S; Mohammed, Imran; Dua, Harminder S
Abstract : Aims: To demonstrate and characterise distinct subepithelial compact nerve endings (CNE) at the human corneoscleral limbus. Methods: Ten fresh human donor corneoscleral discs (mean age, 67 years) and 26 organ-cultured corneoscleral rims (mean age, 59 years) were studied. All samples were subjected to enzyme histochemical staining related to endogenous acetylcholinesterase present in nerve tissue and H&E staining. Whole-mount en face imaging with NanoZoomer digital pathology microscope and serial cross-section imaging with light microscope were undertaken. Results: Nerves entering the corneoscleral limbus and peripheral cornea terminate under the epithelium as enlarged multiloculated and multinucleated ovoid structures within a 2 mm zone. They are closely associated with the rete pegs of the limbal palisades and the limbal epithelial crypts, often located within characteristic stromal invaginations of these structures. Their numbers ranged from 70 to 300 per corneoscleral rim. The size ranged from 20 to 100 µm. They had one or more nerve connections and were interconnected to other similar endings and to the limbal nerve plexus. Conclusion: Human corneoscleral limbus demonstrates a population of nerve terminals resembling CNE with distinct morphological features. They are closely associated with the limbal stem cell niches, suggesting a potential contribution to the niche environment.